Polymorphism of xenobiotic biotransformation enzyme genes and their role in early pregnancy loss - S. V. Matoshin; S. V. Shramko (Фундаментальная и клиническая медицина, 2024)
Considering the progressive decrease in the number of women of fertile age, as well as children and adolescents, the primary medical and social task at the present stage is to preserve the reproductive health and life of women, preserving every desired pregnancy. The concept of demographic policy of the Russian Federation for the period until 2025 defines the global national goals, i.e. to increase the total fertility rate by 1.5 times, to reduce maternal and infant mortality by at least 2 times, and to improve the reproductive health of women, children and adolescents. Today every fifth desirable pregnancy ends in early loss, and the rate of miscarriage does not tend to decrease and, in fact, increases every year. Carriage of susceptibility or candidate genes can alter the course of biochemical processes in women and cause early pregnancy losses. According to the literature, the cytochrome P-450 gene (CYP1A1, CYP1B1), xenobiotic detoxification genes (GSTT1, GSTM1, GSTP1) and many others are recognized as candidate genes (genetic markers) associated with reproductive losses. Adverse pregnancy outcome is usually multifactorial; in turn, the combination of polymorphic variants of different candidate genes can increase the risk of early losses. A detailed study of the role of candidate genes with clarity and confirmation of the interest of candidate genes in the development of pregnancy loss is undeniable. In this regard, the interest of many researchers in studying the polymorphism of genes of the xenobiotic biotransformation enzyme system as one of the causal factors of pregnancy failure is understandable. The study of this group of genes is of particular relevance in regions with developed industry and high anthropogenic load. The article is devoted to the analysis of the existing data of foreign and domestic literature sources concerning the relationship between polymorphism of xenobiotic biotransformation system genes and reproductive losses.